Enabling academic entrepreneurship in Malaysian Universities: An organisational perspective. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2007)
Universities in the 21st Century are faced with many challenges which brought about the need to change. These challenges and the need for change have been spurred by the changing role of universities in the society and the pressure to prepare students for a world of lifelong learning, of greater uncertainty and complexity, and greater probability of self employment. Universities are also pressured to play an enhanced role in contributing to international competitiveness of economies particularly via the process of research commercialisation and contribute more to local and regional economic and social development (Ali, 2004; Jain & Yusof, 2007).